Energy and Entropy Equilibrium to Stationary States - Starzak, Michael E. (Springer New York : Imprint: Springer, 2010)
This book is an overview of classical thermodynamics, statistical thermodynamics, non-equilibrium and stationary state thermodynamics. This comprehensive work is the first book outside of specialized monographs to approach flow systems and irreversible thermodynamics for advanced undergraduate or introductory graduate courses in thermodynamics in chemistry, physics, biophysics, and engineering programs. Instructors for those courses will find in this book transparent models that clarify a broad range of difficult physical and mathematical concepts, including: Cooligative properties and solution thermodynamics Chemical potential for equilibrium systems Continuous energy systems Transition to non-equilibrium systems through statistical chemical kinetics Bose-Einstein statistics in conjunction with unimolecular reaction rate theory Irreversible thermodynamics with both time and spatial dependence Basic stationary state processes.